The effective screening tools for detecting hearing loss in elderly population: HHIE-ST Versus TSQ - Nichtima Chayaopas (BMC Geriatrics, 2021)
Abstract Background Globally increasing number of elders is concerned. Hearing loss process in older adults cannot be avoided. An effective screening tool for hearing loss is essential for proper diagnosis and rehabilitation, which can improve QOL in older adults. Methods This prospective-diagnostic test study evaluates the diagnostic value of Thai version of the Hearing Handicap Inventory for Elderly Screening (HHIE-ST) and the Thai Single Question (TSQ) surveys in screening hearing disability in 1109 Thai participants aged 60 years and older in communities in four provinces in Thailand. The HHIE-ST consisted of 10 selected questions from the validated HHIE-Thai version. A TSQ survey was developed to have the same meaning as an English Single Question survey. The participants answered both questionnaires, and a standard audiometry test assessed with air conduction from 250 to 8000 Hz was included as a gold standard. Results The prevalence of hearing disability was 38.34%. The HHIE-ST achieved a sensitivity of 88.96% (95% CI 85.77–91.64) and specificity of 52.19% (95% CI 48.24–56.13) for diagnosis hearing disability in Thai older adults, whereas the TSQ yielded a sensitivity of 88.73% and a specificity of 55.93%. A combined test including the HHIE-ST and TSQ achieved better performance with sensitivity of 85.29% and specificity of 60.13%. Conclusions Either the HHIE-ST or the TSQ is a sensitive and useful tool for screening hearing disability in Thai older adults. Using the HHIE-ST together with the TSQ resulted in a better screening tool for detecting moderate hearing loss older adults who will benefit and recommended for hearing rehabilitation. Trial registration The study is registered with the following number in the Thai Clinical Trials Registry: TCTR20151015003 . Date of registration October 14, 2015.